1997
DOI: 10.1149/1.1837530
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of RuO2 Thin Films Prepared by Hot‐Wall Metallorganic Chemical Vapor Deposition

Abstract: RuO2 thin films were deposited on SiO2/normalSi substrate at low temperatures by hot‐wall metallorganic chemical vapor deposition using the ruthenocene and oxygen gas mixtures. The preferred orientation of films varied from (200) to (101) as the film thickness increases above 150 nm irrespective of the deposition conditions. RuO2 deposition reaction was controlled by gas‐phase mass‐transfer in these experiments. The film resistivity increased with increasing oxygen flow rates. The increase of film resisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 2 publications
2
32
0
Order By: Relevance
“…In the case of ALD, the stability of the adsorbed oxygen layer during the purge step is an additional issue to be considered, and may explain why no RuO 2 was obtained, even if, with CVD, RuO 2 can be deposited at similar temperatures (200±350 C). [38] The adsorbed oxygen layer may also be reduced by the subsequently pulsed RuCp 2 . Surface studies on oxygen adsorption on metallic ruthenium have shown that oxygen chemisorbs dissociatively on a ruthenium surface, already at room temperature, under ultra high vacuum (UHV) conditions [39,40] with a maximum saturated surface coverage of 0.5 monolayers.…”
Section: Film Growthmentioning
confidence: 99%
“…In the case of ALD, the stability of the adsorbed oxygen layer during the purge step is an additional issue to be considered, and may explain why no RuO 2 was obtained, even if, with CVD, RuO 2 can be deposited at similar temperatures (200±350 C). [38] The adsorbed oxygen layer may also be reduced by the subsequently pulsed RuCp 2 . Surface studies on oxygen adsorption on metallic ruthenium have shown that oxygen chemisorbs dissociatively on a ruthenium surface, already at room temperature, under ultra high vacuum (UHV) conditions [39,40] with a maximum saturated surface coverage of 0.5 monolayers.…”
Section: Film Growthmentioning
confidence: 99%
“…[2] Bis(ethylcyclopentadienyl)ruthenium, (C 2 H 5 C 5 H 4 ) 2 Ru, with a molecular structure shown below, is a recently explored CVD precursor to Ru metal and oxide films. [3±8] Among the family of Ru precursors, including ruthenium carbonyls (Ru 3 (CO) 12 ), [9±11] 2 Ru was mainly focused on film growth and properties. [3±8] In view of potential industrial applications and chemical implications related to other ruthenium precursors, we were motivated to examine the ultra-high vacuum (UHV) surface science of this precursor.…”
Section: Introductionmentioning
confidence: 99%
“…However, the residual mass, 37 %, observed at 200 C was significantly higher. The latter is probably due to the formation of less volatile, polynuclear carbido cluster complexes such as [Ru 6 C(CO) 17 ], for which the synthesis involves direct heating of the parent carbonyl complex Ru 3 (CO) 12 . [16] As a result, Ru 3 (CO) 12 should be less suitable for CVD experiments where the facile formation of [Ru 6 C(CO) 17 ] would complicate the chemistry involved in the thin film deposition.…”
Section: Synthesis and Characterization Of The Cvd Source Reagentmentioning
confidence: 99%
“…The latter is probably due to the formation of less volatile, polynuclear carbido cluster complexes such as [Ru 6 C(CO) 17 ], for which the synthesis involves direct heating of the parent carbonyl complex Ru 3 (CO) 12 . [16] As a result, Ru 3 (CO) 12 should be less suitable for CVD experiments where the facile formation of [Ru 6 C(CO) 17 ] would complicate the chemistry involved in the thin film deposition. The encapsulated carbide atom would also increase the final carbon content of the as-deposited thin film through the transition metal-mediated disproportionation of CO, as shown in Equation 2.…”
Section: Synthesis and Characterization Of The Cvd Source Reagentmentioning
confidence: 99%